2016
DOI: 10.1186/s13613-016-0206-9
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of neuromuscular blockade on global and regional lung mechanics, oxygenation and ventilation in pediatric acute hypoxemic respiratory failure

Abstract: BackgroundNeuromuscular blockade (NMB) has been shown to improve outcome in acute respiratory distress syndrome (ARDS) in adults, challenging maintaining spontaneous breathing when there is severe lung injury. We tested in a prospective physiological study the hypothesis that continuous administration of NMB agents in mechanically ventilated children with severe acute hypoxemic respiratory failure (AHRF) improves the oxygenation index without a redistribution of tidal volume V T toward non-dependent lung zones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 48 publications
2
20
0
4
Order By: Relevance
“…After adjustment for baseline P/F, plateau pressure, and the Simplified Acute Physiology Score, the cisatracurium group had a hazard ratio for death at 90 days of 0.68 (95% CI, 0.48-0.98) compared with the placebo group. Early use of NMBAs was also associated with decreased organ system dysfunction, less air leak, and a decreased pro-inflammatory response [308]. These findings remained consistent when combined with earlier smaller studies from the same group of investigators in a meta-analysis.…”
Section: S36supporting
confidence: 81%
“…After adjustment for baseline P/F, plateau pressure, and the Simplified Acute Physiology Score, the cisatracurium group had a hazard ratio for death at 90 days of 0.68 (95% CI, 0.48-0.98) compared with the placebo group. Early use of NMBAs was also associated with decreased organ system dysfunction, less air leak, and a decreased pro-inflammatory response [308]. These findings remained consistent when combined with earlier smaller studies from the same group of investigators in a meta-analysis.…”
Section: S36supporting
confidence: 81%
“…Valentine et al, 35 Gainnier et al, 57 Forel et al, 58 Papazian et al, 59 Murray et al, 60 Wilsterman et al 62 (continued) recommendations, along with those for adjunctive therapies covered in the following section, are summarized in Table 2.…”
Section: Rimensberger Andmentioning
confidence: 99%
“…A prospective physiologic study by Wilsterman et al showed improved OI in pediatric patients with acute hypoxemic respiratory failure who received continuous NMB during mechanical ventilation. 62 Based largely on the available adult data, PALICC recommends considering NMB in children with PARDS if sedation alone is inadequate to achieve effective mechanical ventilation, targeting the minimal effective dose. 35…”
Section: Recruitment Maneuversmentioning
confidence: 99%
“…Intravenous neuromuscular blockade was started if the peak inspiratory pressures approximated 28-30 cmH2O, and the patient was hypoxemic and continued to show excessive work of breathing despite adequate sedation [23] . .08] days, p = 0.348).…”
Section: Management and Outcomesmentioning
confidence: 99%